Structural framework, crustal shortening and Cenozoic exhumation in the eastern Himalaya: A review. (December 2021) - Goswami, Tapos Kumar; Bezbaruah, Devojit; Mahanta, Bashab Nandan; Sarmah, Ranjan Kumar
Abstract: Significant variations (along strike) in deformation style, rate of crustal shortening, erosion and exhumation are observed in the eastern Himalayan orogen. We review the literature to understand the crustal shortening due to the collision of the Indian and Asian plates accommodated through major thrusts and shear zones. The Main Central Thrust (MCT) is a major thrust system along which hundreds of kilometres of crustal shortening have been estimated in eastern Himalaya. Recesses of MCT in the form of culmination zones are formed in Sikkim-Darjeeling, Bhutan and Arunachal Himalayas. Antiformal stacks in the hanging wall of MCT indicate faster exhumation compared to slow exhumation in the synform at the orogenic front. The folded nappes in eastern Himalaya depict the interplay of erosion and exhumation. We observe that the lateral variation in the orogen may also be attributed to transverse structures that divide the mountain range into sectors with dissimilar structural geometry. The strain variation reflected through crustal shortening along the orogen is accommodated by transverse structures like strike-slip faults. Many of these transverse structures are loci of major earthquakes that struck the region in the past. In the Sub-Himalaya, signatures such as changes of the river courses, upliftment of the terraces and active fault scarps indicate that the south directed post collisional compression is accommodated through the slip along the Himalayan Frontal Thrust (HFT) and its splays. Highlights: We review the relevant literature to know the structural architecture of the eastern Himalaya. Total crustal shortening across the MCT is estimated to be maximum in Arunachal Himalaya. Rapid exhumation of the core of the eastern Himalayan syntaxis taking place from late Miocene. South propagating deformation keeps the mountain front active along the HFT in eastern Himalaya. Major orogen transverse strike slip faults in the eastern Himalaya are seismogenic.